Association of Lipid Profile with Type 2 Diabetes in First-Degree Relatives: A 14-Year Follow-Up Study in Iran - Sadeghi E (Dove Medical Press, 2020)
Erfan Sadeghi,1,2 Sayed Mohsen Hosseini,1 Mehrdad Vossoughi,3 Ashraf Aminorroaya,4 Massoud Amini4 1Department of Epidemiology and Biostatistics, School of Health, Isfahan University of Medical Sciences, Isfahan, Iran; 2Student Research Committee, School of Health, Isfahan University of Medical Sciences, Isfahan, Iran; 3Oral and Dental Disease Research Center, Department of Dental Public Health, School of Dentistry, Shiraz University of Medical Sciences, Shiraz, Iran; 4Isfahan Endocrine and Metabolism Research Center, Isfahan University of Medical Sciences, Isfahan, IranCorrespondence: Sayed Mohsen HosseiniDepartment of Epidemiology and Biostatistics, School of Health, Isfahan University of Medical Sciences, Isfahan 81746-73461, IranTel +98 313 792 3251Fax +98 311 668 2509Email hosseini@hlth.mui.ac.irPurpose: Dyslipidemia is claimed to be associated with an increased risk of type 2 diabetes mellitus (T2DM). However, first-degree relatives (FDRs) of patients with T2DM are reported to be at higher risk. The aim of this study was to evaluate the association between serum lipid profile and T2DM incidence in FDRs.Patients and methods: Information on 1222 T2DM FDRs during 14 years of follow-up was retrieved. All individuals were examined for diabetes status and dyslipidemia once a year. We used a Bayesian joint longitudinal-survival model to assess the association.Results: Our data showed that a 10 mg/dL increase in triglycerides (TG), very-low-density lipoprotein (VLDL), and non-high-density lipoprotein (non-HDL) cholesterol levels during the follow-up period was associated with an increased risk of diabetes by 5%, 29%, and 6.6%, respectively. Moreover, for every one-unit increase in the TG to HDL ratio, the T2DM incidence increased by 35%. Subgroup analysis also showed that the increased risk of diabetes was significant only in female FDRs, so that a 10 mg/dL increase in TG and VLDL cholesterol level and a one-unit increase in TG to HDL ratio in female FDRs resulted in an increased risk of diabetes by 7.8%, 46%, and 64%, respectively. However, analysis of HDL, low-density lipoprotein (LDL), total cholesterol (TC), TC to HDL, and LDL to HDL cholesterol levels/ratios did not find any statistically significant associations.Conclusion: Increases in TG, VLDL, non-HDL cholesterol level, and TG to HDL ratio are associated with an increased risk of T2DM in FDRs, especially in female FDRs.Keywords: diabetes mellitus, joint model, longitudinal studies, survival